Development of Digital Transformation Instruments and Partnership For MSMEs in Denpasar City - Yudha, Bagus Arista; Reganata, Gde Palguna (Journal of Economics and Public Health, 2023)
SMEs are a type of industry that is more customer focused and have better opportunities if supported by the use of digitalization transformation and collaboration with partnerships that can provide support for the development of an SME. This research was conducted to analyze the digital transformation and partnership questionnaire in SMEs. Method: The questionnaire will be analyzed using validity and reliability tests, where validity tests include content validity, face validity, Focus Group Discussion and construct validity. The number of respondents in the validity test was 5 respondents and 30 respondents in the reliability test. The results of the questionnaire analysis in the content validity analysis test were declared valid with an items content validity index (1-CVI) value of ≥ 0.78. In the results of face validation, it was found that the statement items in the questionnaire described the construct well. The results obtained after the focus group discussion process were that the majority of panelists agreed on the statements made with a minimum value of 2 which means "easy to understand" and a maximum value of 3 which means "very easy to understand". The number who got a score of 2 (easy to understand) was 25% and the number who got a score of 3 (very easy to understand) was 75%. The reliability test obtained a Cronbach alpha value of 0.940; So according to table 4 above, this value means Very Reliable and suitable to be distributed to respondents. From the results of the table analysis, all question items are reliable. The instruments analyzed in this research, namely the digitalization transformation and partnership instruments, can be categorized as valid and reliable instruments so they can be used as research tools.